2015
DOI: 10.1097/jim.0000000000000234
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Levels in Patients with Type 2 Diabetes Mellitus

Abstract: BackgroundVitamin D may influence many diseases, including type 2 diabetes mellitus.Patients and MethodsWe studied serum levels of 25-hydroxyvitamin D (25(OH)D) and associated characteristics in type 2 diabetic outpatients with pharmacologic treatment attended in internal medicine offices in a first-level hospital from Extremadura (Southern Spain).ResultsWe included a total of 103 patients. Seventy-two patients (69.9%) had serum levels of 25(OH)D lower than 20 ng/mL. There was inverse correlation between serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
(36 reference statements)
0
17
0
1
Order By: Relevance
“…The discrepancy between the findings of epidemiologic surveys and intervention studies regarding Vitamin D and type 2 diabetes is remarkable. Most cross-sectional studies found a revers relationship between 25(OH)D serum concentrations and type 2 diabetes[ 9 20 21 22 ] while others revealed an independent inverse association only in women. [ 23 24 25 ] One meta-analysis including twenty-one prospective studies showed that there was inverse association between serum 25(OH)D levels and incidence of type 2 diabetes after adjusting for BMI and intermediate biomarkers (included 4996 incident cases of diabetes and 76220 nondiabetic controls).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy between the findings of epidemiologic surveys and intervention studies regarding Vitamin D and type 2 diabetes is remarkable. Most cross-sectional studies found a revers relationship between 25(OH)D serum concentrations and type 2 diabetes[ 9 20 21 22 ] while others revealed an independent inverse association only in women. [ 23 24 25 ] One meta-analysis including twenty-one prospective studies showed that there was inverse association between serum 25(OH)D levels and incidence of type 2 diabetes after adjusting for BMI and intermediate biomarkers (included 4996 incident cases of diabetes and 76220 nondiabetic controls).…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] However, in studies examining prediabetic patients, improvement in HbA1c and FPG in Vitamin D receiving groups bordered on statistical significance. [ 21 ] Possible explanation for lack of an effect found in intervention studies might be related to the patient characteristic, duration of the study, dosage, and other confounding variables.…”
Section: Discussionmentioning
confidence: 99%
“…Wenzhou, which is a southeastern coastal city of China, is in temperate zones (23.5°–66.5°). It has been reported that vitamin D deficiency was independently correlated with T2D, due to increased insulin resistance and β-cell malfunction [ 22 , 23 ]. Although 25(OH)D deficiency is usually detected in T2D patients, especially in those who are obese and in which insulin resistance is the most common finding, nutritional status of hypovitaminosis D was widely observed in non-obese diabetes by our pilot study.…”
Section: Discussionmentioning
confidence: 99%
“…Low concentration of vitamin D is associated with T2DM patients. e serum concentration of 1,25(OH)D in 69.9% of 103 patients is lower than 20 ng/ml and negatively correlated with hemoglobin A1C and insulin resistance [105]. In adults aged over 45 years, vitamin D deficiency is significantly associated with occurrence of T2DM [106].…”
Section: Vitamin D Deficiency With Lipidmentioning
confidence: 99%